Cooperative Palladium/Isothiourea Catalyzed Enantioselective Formal (3+2) Cycloaddition of Vinylcyclopropanes and α, β‐Unsaturated Esters. (28th April 2022) - Bitai, Jacqueline; Nimmo, Alastair J.; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract: A protocol for the enantioselective synthesis of substituted vinylcyclopentanes has been realised using cooperative palladium and isothiourea catalysis. Treatment of vinylcyclopropanes with Pd(PPh3 )4 generates a zwitterionic π‐allyl palladium intermediate that intercepts a catalytically generated α, β‐unsaturated acyl ammonium species prepared from the corresponding α, β‐unsaturated para ‐nitrophenyl ester and the isothiourea ( R )‐BTM. Intermolecular formal (3+2) cycloaddition between these reactive intermediates generates functionalised cyclopentanes in generally good yields and excellent diastereo‐ and enantiocontrol (up to >95 : 5 dr, 97 : 3 er), with the use of LiCl as an additive proving essential for optimal stereocontrol. To the best of our knowledge a dual transition metal/organocatalytic process involving α, β‐unsaturated acyl ammonium intermediates has not been demonstrated previously. Abstract : Cooperative palladium and isothiourea catalysis allows the formal (3+2) cycloaddition of vinylcyclopropanes and α, β‐unsaturated esters to generate functionalized cyclopentanes via an α, β‐unsaturated acyl ammonium intermediate with the addition of LiCl crucial to obtain high product diastereo‐ and enantioselectivity.